Review on Desirable Microbial Phytases as a Poultry Feed Additive: Their Sources, Production, Enzymatic Evaluation, Market Size, and Regulation - Olyad Erba Urgessa; Rufael Koyamo; Hunduma Dinka; Ketema Tafess; Mesfin Tafesse Gemeda (International Journal of Microbiology)
Poultry’s digestive tract lacks hydrolytic phytase enzymes, which results in chelation of dietary minerals, vital amino acids, proteins, and carbohydrates, phytate-phosphate unavailability, and contamination of the environment due to phosphorus. Therefore, it is necessary to use exogenous microbial phytases as feed additive to chicken feed to catalyze the hydrolysis of dietary phytate. Potential sources of microbial isolates that produce desired phytases for chicken feed supplementation have been isolated from agricultural croplands. It is achievable to isolate phytase-producing bacteria isolates using both broth and agar phytase screening media. Potential substrates for submerged fermentation (SmF) for bacterial phytase production and solid-state fermentation (SSF) for fungal phytase production include rice and wheat bran. Following fermentation, saturated ammonium sulphate precipitation is typically used to partially purify microbial culture filtrate. The precipitate is then desalted. Measurements of the pH optimum and stability, temperature optimum and stability, metal ions stability, specificity and affinity to target substrate, proteolysis resistance, storage stability, and in vitro feed dephosphorylation are used to perform an enzymatic evaluation of phytase as an additive for poultry feed. The growth of the feed phytase market is primarily due to the expansion of chicken farms to meet the demand for meat and eggs from humans. The Food and Drug Administration in the USA and the European Food and Safety Authority are primarily in charge of putting rules pertaining to feed phytase use in chicken feed into effect. Conclusively, important components of the production of phytase additives for poultry feed include identifying a reliable source for potential microbe isolation, selecting an economical method of phytase production, thoroughly characterizing the biochemical properties of phytase, and comprehending the size and regulation of the current feed phytase market.